Pemphigus Vulgaris: Present and Future Therapeutic Strategies - Dario Didona; Giovanni Paolino; Giovanni Di Zenzo; Biagio Didona; Riccardo Pampena; Matteo Riccardo Di Nicola; Santo Raffaele Mercuri (Mattioli1885, 2022)
Pemphigus vulgaris (PV) belongs to the group of autoimmune blistering diseases. PV can affect not only mucous membranes, but also the skin and it is characterized by serum IgG autoantibodies against desmoglein 1 and 3, two major components of desmosomes. The introduction of glucocorticoids improved dramatically the prognosis of patients affected by PV.  However, long-term use of high dose corticosteroids and adjuvant steroid-sparing immunosuppressants can lead to several adverse events. Rituximab, a chimeric anti-CD20 monoclonal antibody, has been recently approved as in-label therapy for PV, leading to an improvement of the prognosis and higher remission rate. Furthermore, other anti B-cell therapies and several anti-CD20 biosimilars have been introduced in the clinical practice. We focused on present and future therapeutic approaches in PV